A qualitative study of service users' experiences of mental health nurses' knowledge and skills in relation to medication. Issue 4 (15th December 2020) - Pearson, Mark; Sibson, Tara; Carter, Timothy
Abstract: Introduction: The role of the mental health nurse in relation to medications remains complex. Despite an increasing focus on pharmacology within pre‐registration nurse education, there is limited research exploring how mental health service users experience mental health nurses' knowledge and skills in relation to medication. Aim: To explore the experiences of service users working with mental health nurses, in relation to the nurses' knowledge and skills associated with medicines management. Method: The research prioritized the principles of co‐production and was undertaken collaboratively with a researcher with lived experience. Data were collected via semi‐structured interviews with individuals who have accessed UK mental health services. Interviews were audio‐recorded, transcribed verbatim and subjected to thematic analysis. Results: Three themes were generated from the data: inconsistencies in knowledge and practice, holistic therapeutic engagement and dialogical approach to medicines. Discussion: Service users may have a sense of uncertainty around the role of the nurse, potentially resulting in frustration and anxiety. However, mental health nurses also possess unique skills in relation to medicines management. Implications for practice: The findings emphasize that service users value not only pharmacological knowledge but also unique skills in facilitating dialogue, prioritising shared decision‐making and practical support in medicines optimization.